Aneurisma ventricular izquierdo gigante con intenso contraste espontáneo, sin trombo - Dinca, Ramona; Diaconu, Rodica; Ungureanu, Anda; Donoiu, Ionut (CorSalud, 2019)
Aneurisma ventricular izquierdo gigante con intenso contraste espontáneo, sin trombo